Investment risk management - Baker, H. Kent (Harold Kent), 1944-; Filbeck, Greg (Financial markets and investments series., 2015)
All investments carry with them some degree of risk. In the financial world, individuals, professional money managers, financial institutions and many others encounter and must deal with risk. The main purpose of 'Investment Risk Management' is to provide an overview of developments in risk management and a synthesis of research involving the latest developments in the field.